2013
DOI: 10.1111/1469-0691.12120
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of invasive fungal disease after unmanipulated haploidentical stem cell transplantation was significantly higher than that after HLA-matched sibling transplantation

Abstract: The aim of this study was to determine the incidence, clinical features and outcome of invasive fungal disease (IFD) after either unmanipulated haploidentical haematopoietic stem cell transplantation (HSCT) or human leukocyte antigen (HLA)-matched sibling HSCT. This was a head-to-head comparative study performed at a single centre. Patients were admitted between 2007 and 2010, and IFD was evaluated according to the revised EORTC/MSG criteria, with only proven and probable cases included. Of the 1042 consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Some articles have already suggested that the development of acute GvHD is a risk factor for opportunistic infection, such as invasive fungal disease and CMV reactivation. 15,19,28 Our previous study also suggested that although the incidence of grade 2-4 acute GvHD was similar between haploidentical HSCT and HLA-identical sibling HSCT, the incidence of grade 1-4 acute GvHD was significantly higher after haploidentical HSCT than after HLA-identical sibling HSCT (Po0.0001) that increased the use of immunosuppressive agents after haploidentical HSCT compared with HLA-identical sibling HCST; this course finally led to an increased incidence of infection. 21 Therefore, the cause of mortality for patients who had both GvHD and infection was classified according to the main and direct causes of mortality in this study.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Some articles have already suggested that the development of acute GvHD is a risk factor for opportunistic infection, such as invasive fungal disease and CMV reactivation. 15,19,28 Our previous study also suggested that although the incidence of grade 2-4 acute GvHD was similar between haploidentical HSCT and HLA-identical sibling HSCT, the incidence of grade 1-4 acute GvHD was significantly higher after haploidentical HSCT than after HLA-identical sibling HSCT (Po0.0001) that increased the use of immunosuppressive agents after haploidentical HSCT compared with HLA-identical sibling HCST; this course finally led to an increased incidence of infection. 21 Therefore, the cause of mortality for patients who had both GvHD and infection was classified according to the main and direct causes of mortality in this study.…”
Section: Discussionmentioning
confidence: 90%
“…Our study also suggested that infection was the most common cause of mortality after haploidentical HSCT (49.5%) but the second most common cause of mortality after HLA-identical sibling HSCT (39.2%). Our previous studies suggested that compared with HLA-identical sibling HSCT, haploidentical HSCT increased the incidence of invasive fungal disease (7.1% vs 3.3%, P = 0.007), post transplant lymphoproliferative disease (2.3% vs 0.4%, Po0.05) and CMV disease (8.7% vs 0.0%, P = 0.004) [15][16][17] that are usually associated with a higher risk of mortality after transplant. [16][17][18][19] Moreover, our previous study found that the T-cell subset and dendritic cell subgroup counts, especially CD8 + , CD4 + and CD4 + naive T cells, within the first 90 days post transplant were significantly lower in patients receiving haploidentical HSCT than in HLA-identical sibling HSCT (Po0.05).…”
Section: Discussionmentioning
confidence: 96%
“…Individual risk factors include: older age; use of broad-spectrum antibiotics (and the effect on gut microbiota); iron overload; use of central venous catheter; diabetes; prior IFI (or species colonization); and lower respiratory tract infection [17,18]. Additionally, patients receiving transplantation from a haploidentical donor have been shown to be at an elevated risk of IFI compared with HLA-matched siblings [19]. Furthermore, the condition of the patient at the time of infection (as measured by Acute Physiology and Chronic Health Evaluation II scores) [20] or at the time of transplant (as measured by the hematopoietic cell transplantation-specific comorbidity index) [21] are considered to be important predictors of patient outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Invasive fungal disease (IFD) remains a major cause of morbidity and mortality after allogeneic hematopoietic stem cell transplantation (allo-HSCT) (1); aspergillosis is the most common IFD infection among HSCT recipients (2,3). The most common form of disease due to Aspergillus species in immunocompromised patients is invasive pulmonary aspergillosis (IPA), which mainly involves the lung parenchyma (4), the development of invasive tracheobronchial aspergillosis (ITBA) and invasive laryngeal aspergillosis is rare; however, the development of fulminant ITBA is associated with a serious prognosis (5,6).…”
Section: Introductionmentioning
confidence: 99%